2008
DOI: 10.1002/bdd.618
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of the analogs at C3 and C5 of m‐nifedipine in beagle dogs

Abstract: The prototype 1,4-dihydropyridine (1,4-DHP) nifedipine, indicated for the management of hypertension and angina pectoris, has disadvantages including photodegradation and a short half-life. Several newer 1,4-DHPs, including m-nifedipine and its analogs at the C3, C5 position such as MN9201, MN9202 and MN9203, have been designed to offset these problems. The aim of this study was to investigate the pharmacokinetic characteristics of these derivatives to provide reference for their further evaluation and modific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…These results correlate with a recent study that showed rapid loss of vasculoprotective effect following the withdrawal of nifedipine, which was expressed in systolic blood pressure returning back to abnormal values in SHR within 24 h. 58 One possible reason was that nifedipine, as an L-type Ca 2+ channel antagonist, is reported to have an initial disadvantage of shorter half-life in vivo. 59 The results demonstrated that there were different mechanisms between fucoidan and nifedipine. In addition, further research on possible reasons for fucoidan's effective and prolonged chronic blood pressure modulation is necessary.…”
Section: Discussionmentioning
confidence: 94%
“…These results correlate with a recent study that showed rapid loss of vasculoprotective effect following the withdrawal of nifedipine, which was expressed in systolic blood pressure returning back to abnormal values in SHR within 24 h. 58 One possible reason was that nifedipine, as an L-type Ca 2+ channel antagonist, is reported to have an initial disadvantage of shorter half-life in vivo. 59 The results demonstrated that there were different mechanisms between fucoidan and nifedipine. In addition, further research on possible reasons for fucoidan's effective and prolonged chronic blood pressure modulation is necessary.…”
Section: Discussionmentioning
confidence: 94%
“…The concentration of AMP, UTP and ATP in patient plasma was measured as our protocol 19 with modification of protocol. 20,21 Briefly, venous blood was collected at admission (within 2 hours before coronary angiography).…”
Section: Preparation Of Blood Samples and Measurement Of Plasma Nuclementioning
confidence: 99%
“…MN9202 has a chiral carbon at position 4 of the dihydropyridine ring and shares a similar structure with nitrendipine, except for the number of carbons at position 3. Earlier studies in dogs have revealed that MN9202 has beneficial effects on the smooth muscle and myocardium 7,8 . In addition, it has been shown that MN9202 concentration‐dependently relaxes rat and rabbit thoracic arteries, 9 an effect that is endothelium independent.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies in dogs have revealed that MN9202 has beneficial effects on the smooth muscle and myocardium. 7,8 In addition, it has been shown that MN9202 concentrationdependently relaxes rat and rabbit thoracic arteries, 9 an effect that is endothelium independent. MN9202 also has favourable pharmacokinetic characteristics.…”
Section: Introductionmentioning
confidence: 99%